Dampak Pesan Campaign Love Myself terhadap Pentingnya Kesehatan Mental Remaja - Damanik, Retno Permatasari; Nursanti, Siti; Utamidewi, Wahyu (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
In 2017 BTS released a campaign with UNICEF "love myself" which aims to influence fans to love themselves, spread positivity around and make the world safe for the younger generation. The research entitled Dampak Pesan Campaign Love Myself terhadap Kesehatan Mental Remaja was conducted to see how much impact the love myself campaign message has on adolescent mental health in ARMY aged 20-23 years. An explanatory survey was used in this quantitative research project. Uses and Effect Theory is the theory put to use. 100 persons made up the study's population. Distribution of surveys using the Likert scale, simple linear regression, and hypothesis testing using the coefficient of determination (R2) were used to gather the data. According to the findings, neither the message variable from the "love yourself" campaign nor its impact on variable Y (adolescent mental health) had any beneficial effects. Only 0.00009% of the message variable's effect was found in this analysis, with the remaining influence coming from other factors that were not included. Keywords: Love Myself Campaign, Adolescent Mental Health, Uses and Effect